High-precision mass measurements of 203-207Rn and 213Ra with SHIPTRAP - Droese, Christian; Ackermann, D.; Andersson, L. -L.; Blaum, Klaus; Block, M.; Dworschak, M.; Eibach, Martin Andreas; Eliseev, Sergey; Forsberg, U.; Haettner, E.; Herfurth, F.; Heßberger, F. P.; et al. (The European physical journal. A, Hadrons and nuclei, 2013)
The masses of the nuclides 203-207Rn and 213Ra were measured directly for the first time with the Penning-trap mass spectrometer SHIPTRAP at GSI Darmstadt. The results confirm the previously determined mass values. The mass uncertainties for 205Rn and 213Ra were significantly reduced. The results are relevant for the investigation of the nuclear shell structure between N = 82 and N = 126 . As an indicator of structural changes the two-neutron separation energies $ S_{2n}(Z,N)$have been studied.